Struktur Vegetasi dan Simpanan Karbon Sedimen Kawasan Regenerasi Mangrove Avicennia lanata (Ridley). di Pesisir Kabupaten Muna - La Ode Abdul Fajar Hasidu; Arif Prasetya; Al Tafakur La Ode (University of Halu Oleo, 2021)
This study aimed to determine the structure and composition of natural regenerated mangrove, also to analyze these soil C and N content. This study was conducted in natural regenerated mangrove at in-active pond in Muna Regency, Southeast Sulawesi on June-August 2021. The data collection of mangrove vegetation by quadratic transect method, prependicuar to the river, with 6 subplots sized 100m2. Species identification according to Panduan Pengenalan Mangrove Indonesia, by Noor YR et al. 2006. Meanwhile, the methods for sediment collection was done by purposive sampling to determine corring site. The sediment was collected by Peat Auger Set for 50 cm of depth. The sediment sample then separated based on depth i.e. 0-10 cm, 10-20 cm, 20-30 cm, 30-40 cm, and 40-50 cm. The samples were dried with temperature 65oC during 10 days. The C and N content were analyzed by Spectrofotometer. Moreover, water content as well as bulk density was determined. The statistical analysis of One Way-Anova was done to determine the differences of bulk density, water, C, and N content on each soil layer.The result showed that the structure and composition of mangrove which found in this location was weaning mangrove (DBH < 10cm). The class of DBH size was dominated by 3,00cm - 3,99 cm (81 ind), 2,00cm – 2,99cm (62 ind), 4,00cm – 4,99cm (52 ind), 5,00cm – 5,99cm (42 ind), 7,00cm – 7,99cm (32 ind), and 6,00cm – 6,99cm (26 ind) respectively. The class of DBH size of 8,00 and 9,00 were found in small amount. The total density of vegetation was categoryzed into high density category, based on Kepmen LH No 201, year 2004 (5183,33 ind/ha). The vegetation formed into the early growing stage. The result of water content, and bulk density showed various results. The highest water content was on the surface layer of soil (0-10 cm) was 35,39±8,61%.Meanwhile, the highest bulk density was on the 20-30 cm of soil layer, was 1,49±0,29 g/cm3. The result of C and N content showed various results on each soil layer. The highest of C content was on the surface layer (0-10 cm), was 2,13±0,76%, and the lowest was on 30-40 cm of soil layer, was 1,72±0,13%. In the other hand, the highest N content was on 40-50 of soil layer, was 0,82±0,29%, and the lowest was on 30-40 cm of soil layer, was 0,57±0,14%. Although there were difference of water content, bulk density, C, and N content on each soil layer, but these differences was not significant statistically (α > 0,05). Commonly, the A. lanata species was dominated in this in-active pond area. It was caused by the environmental condition was enclosed because of soil bund wall of pond, so it is confined to another species to regenerate naturally in this area. Furthermore, the structure of A. lanata seeds which have small size facilitates its spread by the current, thus providing a opportunity for seeds spreaded, growth and regenerated naturallyKey word: A. lanata, natural regeneration, C sedimen, N content